2015
DOI: 10.3892/or.2015.4508
|View full text |Cite
|
Sign up to set email alerts
|

Marginal zinc intake reduces the protective effect of lactation on mammary gland carcinogenesis in a DMBA-induced tumor model in mice

Abstract: Breastfeeding can reduce breast cancer risk; however, unknown factors modify this protective effect. Zinc (Zn) modulates an array of cellular functions including oxidative stress, cell proliferation, motility and apoptosis. Marginal Zn intake is common in women and is associated with breast cancer. We reported that marginal Zn intake in mice leads to mammary gland hypoplasia and hallmarks of pre-neoplastic lesions. In the present study, we tested the hypothesis that marginal Zn intake confounds the protective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…and large (N8.5 cm 3 ). adult female C57/Bl6 mice, leading to shorter tumor latency, and greater incidence of tumors in these animals, when DMBA was administered to dams [20,37]. Although some studies have indicated that nutritionally induced poor early growth is linked to increased susceptibility of mammary tumor development in female Wistar rats [38,39], the altered body weight and mammary gland outgrowth induced by dietary zinc deficiency did not alter the development of chemically induced mammary tumors in our study.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…and large (N8.5 cm 3 ). adult female C57/Bl6 mice, leading to shorter tumor latency, and greater incidence of tumors in these animals, when DMBA was administered to dams [20,37]. Although some studies have indicated that nutritionally induced poor early growth is linked to increased susceptibility of mammary tumor development in female Wistar rats [38,39], the altered body weight and mammary gland outgrowth induced by dietary zinc deficiency did not alter the development of chemically induced mammary tumors in our study.…”
Section: Discussioncontrasting
confidence: 62%
“…These findings may be explained by the evidence that the intracellular increase of zinc is essential for cell proliferation, since its absence is related to tumor cells arrest in S-phase [41,42]. On the other hand, excessive intracellular zinc accumulation is cytotoxic and presents a potential prooxidant activity leading to cellular oxidative stress and increased risk of mammary cancer development in mice [20,37,43]. In the present study, the dietary zinc supplementation (~fivefold more than the control) could have been cytotoxic to the mammary tissue, corroborating to other studies [44,45] and modifying carcinogenic action of DMBA on this tissue leading to higher number of mammary tumors in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Feeding the ZM diet for this length of time to mice alters whole-body Zn balance by affecting fertility, testicular Zn concentration, sperm activity, and Zn concentration in milk of lactating female 2224 . Although this specific ZM diet does not appear to alter plasma Zn levels 2225 , it has been reported to lower hepatic Zn content in the non-stressed state 22 . Body weights and food intake were recorded weekly during the diet protocol.…”
Section: Methodsmentioning
confidence: 71%
“… 164 , 171 In support of this, the incidence of mammary tumors in primiparous mice exposed to a carcinogen is lower in mice fed a zinc adequate diet than in mice fed a marginally zinc-deficient diet, similar to the zinc-deficient diets often consumed by humans. 172 …”
Section: Zinc Transporters and Zinc Signaling In Cancermentioning
confidence: 99%